“Intervención en el espacio urbano-arquitectónico del Teatro Juan Benigno Vela” - Rivadeneira Poveda, Daniel Mateo (2023)
This project research is focused on carrying out an integral intervention in the Juan Benigno Vela Theater and its urban environment. This study addresses various issues through a comprehensive analysis at different scales, from a macro perspective to a specific level of intervention, in order to obtain accurate and meaningful results. In order to achieve this objective, a mixed approach methodology is used, which delves into the study of the theatrical space and its context. In order to adequately support the intervention proposal, an analysis is complemented with a thorough review of the theoretical framework, addressing both a historical and conceptual analysis of the theatrical space. Likewise, the relevance of theater in the social and cultural context of cities is examined, understanding its historical and conceptual dimension in the configuration of the intervention proposal. The proposal is oriented towards the integral improvement of the Juan Benigno Vela Theater, responding to its current situation of neglect and abandonment, which has had a negative impact on the cultural life of the community and the city in general. Based on its belonging to the modern movement, we seek to enhance the historical and cultural value of the building by revaluing its legacy in the architectural and theatrical context. To achieve an effective intervention, actions are proposed to improve the accessibility and functionality of the theatrical space and its urban environment, encouraging appropriation and social activation in the place, from the creation of pedestrian public space, which serves as an opportunity to promote and revitalize urban life and cultural connections in the space and the city.